Structure and properties of commercially pure titanium nitrided in the plasma of a low-pressure gas discharge produced by a PINK plasma generator; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Ivanov Yu. F. Yuriy Fedorovich; Akhmadeev Yu. H.; Lopatin I. V.; Petrikova E. A.; Krysina O. V.; Koval N. N. (2015, 2015)
Title screen